Impact of tectonic deformation on coal methane adsorption capacity - Wu Li; Bo Jiang; Yan-Ming Zhu (Adsorption Science & Technology)
Tectonic deformation can cause significant changes in the physical and chemical structures of coal by damaging the macrostructure and macromolecular composition. For thorough research on the coal tectonic deformation impacts on gas adsorption capacity, this paper collected and summarized the parameters of experimental adsorption isotherms and coal macerals, conducted proximate and ultimate analyses, and systematically discussed the adsorption properties of different structures of coals and the influence of temperature and pressure on coal adsorption. Furthermore, the semi-quantitative relationships between the structural parameters of coal and its methane adsorption capacity are explored. The results show that (1) due to different tectonic stresses, the molecular and porous structures of different types of tectonic coal exhibit significant differences (e.g. sample N25, which is in a fault zone, has the highest methane adsorption capacity), and (2) coal methane adsorption capacity decreases along with increasing temperature. At a pressure of 12 MPa, primary coal (N32) showed Langmuir volume (V L ) values of 15.38, 9.58, and 7.86 cm 3 /g and Langmuir pressure (P L ) values of 3.82, 2.07, and 1.81 MPa at temperatures of 30°C, 50°C, and 70°C, respectively. (3) The Langmuir volume appears to have a linear relationship with parameters I D1 /I G , Al/OX, and A-factor, as well as a parabolic curve relationship with f a , thereby illustrating that increases of apparent aromaticity can raise CH 4 adsorption on coal.